The impact of bank liquidity on the Lebanese banks’ risk taking behavior - El Khoury, Rim (2018)
This paper investigates the impact of bank liquidity on the risk-taking behavior using a panel data of audited financial statement of 21 Lebanese commercial banks for the period from 2008 to 2015. Bank risk was measured as risk weighted asset ratio, loan loss provision divided by total assets, and net interest income ratio, while liquidity was measured as liquid asset divided by total assets. To achieve this objective, this study includes control variables and time dummy variables. Three models were tested depending on the definition of risk using the fixed effect model. Our results support the view that bank liquidity increases the bank total risk but decreases the bank lending risk. Furthermore, capital buffers stimulate banks to take more risk and size normally increases bank‟s risk in response to higher liquidity. This conclusion might suggest that higher capital requirements under Basel III are likely to increase bank risk with the implementation of new liquidity ratio. This study provides an understanding between liquidity and bank risk taking which may help regulators to modify the banking regulation in the future when bank liquidity levels change.